2015
DOI: 10.3109/10717544.2015.1043472
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of insulin using PLGA nanoparticles co-modified with cell-penetrating peptides and Engrailed secretion peptide (Sec)

Abstract: Biodegradable polymer nanoparticle drug carriers are an attractive strategy for oral delivery of peptide and protein drugs. However, their ability to cross the intestinal epithelium membrane is largely limited. Therefore, in the present study, cell-penetrating peptides (R8, Tat, penetratin) and a secretion peptide (Sec) with N-terminal stearylation were introduced to modify nanoparticles (NPs) on the surface to improve oral bioavailability of peptide and protein drugs. In vitro studies conducted in Caco-2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Comparing to other routes, and for chronic treatment schedules, oral administration offers comfort and improves patient’s compliance. Recent studies have demonstrated the added-value of loading drugs in PLGA NPs to enhance their oral bioavailability [ 13 , 14 ]. PEG surfacing PLGA NPs have enhanced mucus permeating properties, therefore contributing to increase the drug’s bioavailability after oral administration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to other routes, and for chronic treatment schedules, oral administration offers comfort and improves patient’s compliance. Recent studies have demonstrated the added-value of loading drugs in PLGA NPs to enhance their oral bioavailability [ 13 , 14 ]. PEG surfacing PLGA NPs have enhanced mucus permeating properties, therefore contributing to increase the drug’s bioavailability after oral administration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of research on topics such as liposomes, micelles, and solid lipid nanoparticles have been reported to improve drug solubility (Gao et al., 2012 ; Tapeinos et al., 2017 ; Zhang et al., 2017 ). Currently, the carrier that has been reported to potentially promote drug transport across the membrane mainly includes plant lectins, membrane fusion proteins, and cell-penetrating peptides (CPPs) (Mora et al., 2016 ; Zheng et al., 2016 ; Zhu et al., 2016 ). Among them, CPPs, a series of short peptides, were found to be supremely effective in enhancing penetration through biological membranes for different cargos, such as micelles, liposomes, and solid lipid nanoparticles (Jiang et al., 2012 ; Ramsey & Flynn, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that oral delivery of peptide has been a great continuous challenge due to its poor stability in the GI tract and low permeability through the intestinal epithelium membrane [40,41,42]. Numerous promising strategies have been utilized to circumvent these obstacles [43], including enzyme inhibitors [44] and solid lipid NPs [45] to protect these drugs from enzymatic degradation.…”
Section: Discussionmentioning
confidence: 99%